Bithiophene-Based Donor–π–Acceptor Compounds Exhibiting Aggregation-Induced Emission as Agents to Detect Hidden Fingerprints and Electrochromic Materials - Patrycja Filipek; Magdalena Kałkus; Agata Szlapa-Kula; Michał Filapek (Molecules)
A group of bithiophenyl compounds comprising the cyanoacrylate moiety were designed and successfully synthesized. The optical, (spectro)electrochemical, and aggregation-induced emission properties were studied. DFT calculations were used to explain the reaction’s regioselectivity and to determine the molecules’ energy parameters (i.e., band gaps, HOMO levels, and LUMO levels). The aggregation-induced emission of compounds has been studied in the mixture of DMF (as a good solvent) and water (as a poor solvent), with different water fractions ranging from 0% to 99%. It has been shown that there are differences in the physicochemical properties of the obtained compounds due to the length of the alkyl chain in the ester group. Investigated derivatives were tested for their potential use in visualizing latent fingerprints and electrochromic materials.